2017
DOI: 10.1021/acs.jpcc.7b05534
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and pH-Dependent Dispersion of Highly Purified Multiwalled Carbon Nanotubes Using Polycarboxylate-Based Surfactants in Aqueous Suspension

Abstract: Multiwalled carbon nanotubes (MWCNTs) were synthesized by chemical vapor deposition and subsequently purified by applying a hightemperature annealing process. The annealed material was characterized using Raman spectroscopy. Next, the interaction of the annealed MWCNTs with polycarboxylate (PCE) comb-copolymer surfactants was studied regarding the quality of dispersion in water, with a focus on the influence of the critical parameters temperature and pH. Optical micrographs and integral lighttransmission measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 52 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The anionic surfactant was the commercially available superplasticizer, MasterRheobuild 30 (BASF, Germany), based on sodium ß-naphthalene sulfonic acid formaldehyde. The naphthalene sulfonate was added as surfactant/dispersant for MWCNT dispersion purposes not for rheology and strength modifications, due to its stability and functionality in alkali-activated materials in addition to its dispersion capabilities [35,36,47,[39][40][41][42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anionic surfactant was the commercially available superplasticizer, MasterRheobuild 30 (BASF, Germany), based on sodium ß-naphthalene sulfonic acid formaldehyde. The naphthalene sulfonate was added as surfactant/dispersant for MWCNT dispersion purposes not for rheology and strength modifications, due to its stability and functionality in alkali-activated materials in addition to its dispersion capabilities [35,36,47,[39][40][41][42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…These procedures are far away from real liquid alkaline conditions. For example, one view showed higher dispersibility of MWCNTs in alkaline pH solutions [35], but in contrast, other researchers concluded that CNT suspensions will not maintain the stability in highly alkaline media [36]; or a medium with neutral pH can be an optimum environment for MWCNT dispersion [37]. Simulation of MWCNT exposure to diluted sodium silicate furthermore confirmed the agglomeration and instability of CNTs in such environments [38].…”
Section: Introductionmentioning
confidence: 99%
“…The nanofillers were dispersed in DI water with the aid of a highrange water reducing admixture MasterRheobuild 30 based on naphthalene sulfonate (NS) from BASF, Germany. Ultrasonication was applied in an ice bath [33,34] using a Bandelin Sonopuls 3100 instrument combined with a sonotrode VS70T (Bandelin, Berlin/Germany). An ultrasonication time of only 5 min at 70% was chosen to prevent possible damage to the MWCNT structures [35].…”
Section: Sample Preparationmentioning
confidence: 99%